SAPA 129 sebagai Strategi Pemerintah dalam Memberikan Perlindungan kepada Perempuan dari Kekerasan di Provinsi Aceh - Adella Utami; Bintarsih Sekarningrum; R. Nunung Nurwati (Society, 2025)
This study investigates the role of SAPA 129 as a government-initiated service in safeguarding women who have experienced violence in Aceh Province. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. The findings demonstrate that SAPA 129 facilitates access to legal, psychological, and social assistance while offering an accessible digital reporting system. It has also contributed to raising community awareness of gender-based violence. Nonetheless, its implementation remains challenged by limited digital literacy, inadequate infrastructure, and deeply rooted patriarchal norms. Drawing on structural-functional theory, the service performs both manifest and latent functions within the broader social protection framework. Manifest functions include formal assistance and structured support, while latent functions involve increasing social solidarity and empowering survivors to report abuse. However, the presence of dysfunctions, such as service gaps in remote areas and insufficient human resources, continues to hinder its effectiveness. The study recommends expanding outreach efforts, strengthening interagency coordination, and promoting value transformation through community-based education. These insights are intended to inform more inclusive and responsive gender protection policies while advancing sociological understanding of violence prevention in localized contexts.